1999
DOI: 10.1177/019251399020004005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Noncustodial Fathers' Family and Life Satisfaction From Resource Theory Perspective

Abstract: The study is an exploratory attempt to examine family and life satisfaction of 212 noncustodial fathers 3 years following divorce, using path analysis to validate the hypothesized ordering among six dependent variables suggested by resource theory. Results indicated the significant predictors of family and life satisfaction were perceived economic well-being, cooperative communication during conflict and during coparenting, low importance of resource deprivation, and low frequency of conflict. Involvement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
0
24
0
5
Order By: Relevance
“…Because any significant association found between maternal disclosure about financial concerns and daughter adjustment difficulties could reasonably be accounted for by a third variable that is common in mother‐headed households after divorce—financial deterioration, that variable will be controlled for statistically in selected analyses. To assess financial deterioration, mothers were asked to rate their financial condition since their divorce across six items (e.g., present financial condition, ability to meet expenses, ability to stay out of debt) via a scale adapted from Rettig, Leichentritt, and Statton (1999). Response choices fell on a 5‐point scale from 1 = Much Worse through 5 = Much Better.…”
Section: Methodsmentioning
confidence: 99%
“…Because any significant association found between maternal disclosure about financial concerns and daughter adjustment difficulties could reasonably be accounted for by a third variable that is common in mother‐headed households after divorce—financial deterioration, that variable will be controlled for statistically in selected analyses. To assess financial deterioration, mothers were asked to rate their financial condition since their divorce across six items (e.g., present financial condition, ability to meet expenses, ability to stay out of debt) via a scale adapted from Rettig, Leichentritt, and Statton (1999). Response choices fell on a 5‐point scale from 1 = Much Worse through 5 = Much Better.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, studies based on small samples of divorced fathers have found positive correlations between fathers’ reports of receiving support from, or engaging in cooperative communication with, the custodial mother and fathers’ reports of involvement with nonresident children (Hoffman, 1995; Rettig, Leichtentritt, & Stanton, 1999). Furstenberg and Nord's (1985) national study also found a positive correlation between cooperative coparenting behaviors after divorce and the frequency of contact between nonresident parents and their children.…”
Section: Conceptual Frameworkmentioning
confidence: 98%
“…Esse mesmo ponto de vista foi corroborado por Retting et al 21 . A comunicação cooperativa durante situações de conflito e durante a coparentalidade se revelou um importante preditor de satisfação de vida e de família entre pais (homens) três anos após o divór-cio.…”
Section: Importância Do Conceito De Coparentalidade Para a Pesquisa Eunclassified